Exploring theories and expanding methodologies where we are and where we need to go - Barnartt, Sharon N.; Altman, Barbara Mandell (Amsterdam ; New York : JAI, 2001)
This volume of "Research in Social Science and Disability" focuses attention on the dual themes of theory and methodology that must form a basis for studies of impairment and disability. It addresses issues that include: critiques of current concepts of disability; the fit between sociological role theory and the concept of disability; the operationalization of different definitions of disability; conducting surveys with people with impairments; and, the reliability and utility of several qualitative research methodologies as applied to impairment and disability. Overall, the papers in this volume represent the beginning of a resurgence of interest in social science theories and methodologies within the study of impairment and disability.
Introduction: exploring theories and expanding methodologies; where we are and where we need to go -- The social model of disability: an outdated ideology? -- The conceptualization of disability -- Using role theory to describe disability -- Definitions of disability, and their operationalization, and measurement in survey data: an update -- Examining the fit between deafness and disability -- Methodological issues in the measurement of persons with disabilities -- Measures of functional limitations: the effects of person-level vs. household-level questionnaire design -- Inclusion of disabled populations in interview surveys: review and recommendations -- Interpretive research and people with intellectual disabilities: politics and practicalities -- Problems of methodology in cross-cultural disability studies: an Indian immigrant example -- Content analysis methodology for studying news and disability: case studies from the United States and England -- Case study method for research on disability.
Includes bibliographical references.
Description based on print version record.
Keywords: Disability studies; Sociology of disability; People with disabilities; Disability: social aspects; Social Science -- People with Disabilities; Health & Fitness -- General